HER+ Africa retreat proposal writing and planning workshop report - Ouya, Fredrick; Nchanji, Eileen; Lutomia, Cosmas; Ketema, Dessalegn (2024)
This proposal aims to develop transformative interventions in agri-food systems, emphasizing gender equality and climate resilience. Guided by the funder's mission, our team crafted a structured proposal, with participants assigned specific sections for thorough analysis and alignment with objectives. Extensive literature reviews enriched the proposal with evidence-based approaches. Through efficient collaboration, our diverse team synergized efforts to produce a cohesive proposal, addressing the urgent need for sustainable development and gender-inclusive growth in agri-food systems.